Polymers in biosensors. - Davis, Frank; Higson, Seamus P. J. (Cranfield University, 2007)
This chapter will be devoted to the incorporation of polymers within biosensors, beginning with a history and descriptions of basic sensor formats - while concentrating on optical and electrochemical sensors. Initially the chapter will discuss the incorporation of polymers as simple coatings for biosensors. These coatings are typically used (i) to improve selectivity (by preventing interferents from reaching the active parts of the sensors) and (ii) to improve the biocompatibility of biosensors. Similar coatings which are used as anchors for biomolecules in various techniques will also be discussed. Following this is a section on polymers which have a more active role. Conducting polymers will be discussed and their structures and use in biosensors will be described. A section follows on redox active polymers and their use to 'wire' biological moieties to electrodes. Finally we will discuss molecularly imprinted polymers and their potential to replace biological molecules as active components within biosensors.